The Impact of National Identification Management Policy in Bauchi State - Yakubu , Adamu Suleiman; Ambali, Abdulrauf (Kashere Journal of Politics and International Relations, 2025)
The fact that the National Identity Management Commission Act of 2007 and Mandatory use of the National Identification Number Act 2015 as amended in section 5 states unequivocally that the NIN shall serve as “Foundation Identity" which every agency or institution shall adopt in establishing the “Functional Identity" requirements for its operation. It is to be noted that most of these agencies still compromise the provision of this Act. This may not be far from the fact that some agencies/organisations even institutions still accept other means of identification contrary to the provision of the NIMC Act. This situation of flagrant violation of the NIMC Act 2007 and 2015 present puzzle which needs to be unravelled. The aim of the study was to: identify and critically examine the basic intents of the NIN policy and to assess the level of awareness/willingness of people to enrol in NIN in the study area. Data for the study were both primary and secondary. Two sets of questionnaire were administered to obtain primary data.